Pemikiran Pendidikan Islam Muhammad Abduh - Firdaus, M; Hamzah, Andi Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study aims to determine Muhammad Abduh's Islamic education thoughts. The effort made by Muhammad Abduh was to carry out reforms in the field of education which was motivated by the educational dichotomy at the time. First, Western education-based education whose curriculum is minus religious education. Second, religion-based education minus the general sciences. As a result of the integration of these two types of education, different human characters were born. The first character prefers worldly problems, and the second character only puts forward the problem of ukhrawi. The effort carried out by Muhammad Abduh was by reforming the goals of Islamic education which emphasized aspects of the world and the hereafter by carrying out an integral Islamic education curriculum (a combination of religious and general sciences), as well as effective, varied and innovative teaching methods.